THE METHODOLOGY OF THE WORLD-SYSTEM ANALYSIS: THE PROBLEM OF THE EVENT AND GLOBAL HISTORY IN THE CONTEXT OF HISTORICAL KNOWLEDGE - Валесян, С. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The main methodological characteristics of the world-system analysis, the criticism of the idea of ​​linearity of time in the context of the study of historical systems and their relation to modern historical knowledge are considered in the article. The basic relations of the concepts of event and global history in the context of studying the capitalist world-system are explored.